Layanan Penelusuran Kompleks Berbasis Teknologi Informasi di Perpustakaan - Indah Wijaya Antasari (UPT Perpustakaan UIN Prof. K.H. Saifuddin Zuhri Purwokerto, 2020)
The purpose of this research is to describe complex search services at the IAIN Purwokerto Library related to information technology, where search uses a search tool in the form of computers and networks. Based on several studies of users in the IAIN Purwokerto library, the library developed its services. Using descriptive method, with a source of complex search service form data in 2017-2019. As a result, the development of information technology is coloring the provision of new services, such as bookless library services, e-library services that can be installed via playstore on android devices, international journal services by subscribing to proquest, etc. Librarians are also required to master technology by providing information technology-based services, in this case complex search services. IT-based complex search services are carried out by integrating all digital services in the library to provide answers to the information needs of users.Keywords: service development, complex search service, digital services, information technology, online search